Ring Finger Protein 213 in Moyamoya Disease With Pulmonary Arterial Hypertension: A Mini-Review - Luo, Yuting; Cao, Zhixin; Wu, Shaoqing; Sun, Xunsha (Frontiers in Neurology, 2022)
Moyamoya disease (MMD), most often diagnosed in children and adolescents, is a chronic cerebrovascular disease characterized by progressive stenosis at the terminal portion of the internal carotid artery and an abnormal vascular network at the base of the brain. Recent studies have identified that MMD can affect the extracranial pulmonary artery, presenting as MMD with pulmonary arterial hypertension. Some reports illustrated that Ring finger protein 213 (RNF213), considered to be a novel susceptibility gene for MMD in East Asia, has strong correlations with pulmonary arterial hypertension. Therefore, this review encapsulates current cases of MMD with pulmonary arterial hypertension and discusses MMD with pulmonary arterial hypertension in the aspects of epidemiology, pathology, possible pathogenesis, and clinical manifestations.